Modeling the Distribution of Dominant Hard Ticks in Southeastern Coastal Areas of the Caspian Sea - Sedighe Nabian; Elahe Ebrahimzadeh; Abbas Farahi; Ahmad Ali Hanafi-Bojd (Journal of Arthropod-Borne Diseases)
Background: Ticks are hematophagous arthropods that have direct and indirect effects on hosts, including the transmission of pathogens. An environmental suitability study of some vector species of hard ticks was conducted using the MaxEnt model in the south-eastern region of the Caspian Sea in Iran.